Hubungan Pemahaman Pendidikan Agama Islam Terhadap Pembentukan Karakter Santri di Madrasah Diniyah Nurudz Dzolam Pasuruan - Khanif, Imada Milla Al; Wardani, Dian Kusuma (JoEMS (Journal of Education and Management Studies), 2024)
Indonesia is currently grappling with the erosion of the nation's character. Various incidents in recent years have provided evidence of this. The cultivation of societal character needs to commence at the earliest stages, particularly focusing on children. The formative years, such as childhood or elementary school age, play a pivotal role in shaping an individual's character. Early-molded and ingrained characters tend to retain these traits strongly. Recognizing this, the government of Kab. Pasuruan implemented a policy mandating Madrasah Diniyah (Madin) attendance. This underscores the issue of student morality and ethical deficiency as integral aspects of the broader educational challenge. Hence, a strategic solution is imperative, such as enforcing compulsory education policies for Madrasah Diniyah. The present research seeks to explore the correlation between comprehension of Islamic religious education and the cultivation of core character traits at Madrasah Diniyah Nurudz Dzolam Pasuruan. We will gather data using a quantitative approach through observation and questionnaire methods. The study population consists of 46 students from grades 4, 5, and 6 at Madrasah Diniyah Nurudz Dzolam. The research findings reveal a significant association between comprehension of Islamic religious education and the development of character traits among the students. It can be seen from rxy = 0.385 with p = 0.002 (< 0.05), with low categories.